If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2(2x + -5) = 4 Reorder the terms: 3x + 2(-5 + 2x) = 4 3x + (-5 * 2 + 2x * 2) = 4 3x + (-10 + 4x) = 4 Reorder the terms: -10 + 3x + 4x = 4 Combine like terms: 3x + 4x = 7x -10 + 7x = 4 Solving -10 + 7x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 7x = 4 + 10 Combine like terms: -10 + 10 = 0 0 + 7x = 4 + 10 7x = 4 + 10 Combine like terms: 4 + 10 = 14 7x = 14 Divide each side by '7'. x = 2 Simplifying x = 2
| Y=1(13)+2 | | 67=9x+4 | | x-11=9+3x | | 3x+5=-8(6+5x) | | (X+3)(X+3)=16-2X^2 | | 7x+4y=109.50 | | 48d=32 | | -2-2y+10=0 | | .2x+4=.4x+10 | | 80=38.21+0.50x | | 17+x=10+12 | | 175(431-y)+200y=80625 | | 68-(7x+3)=7(x+5)+x | | mz^2-4mz-32m=0 | | (2-3)=m(4-5) | | 3+10=1 | | 6*1.5*n=9.75 | | 6(4)+4= | | Y=(13)+2 | | 8x+12+2x-9=6x-5 | | -7-5=a | | x^2-13=x-49 | | 4=[9-3(5w+1)]-5w | | 2x+9=23-5x | | 5(3(4)+8)= | | 95=-19a | | 2cos(4x)-(sqrt(3))=0 | | 3(a+1)-5=3a-w | | 4(k+4)=-2(2k-5)-18 | | 5x^2+-10x+-625=-604 | | 5k-3+9+k=180 | | 6u+2-4u-2(-2u-1)=2(u-3) |